The Performance of Teachers as a Factor Associated with Educational Quality in Latin America - Escribano Hervis, Elmys (2018)
The theme of this essay is located in the current studies on the quality of education and, in this case, the quality associated with the teacher's performance, this relationship appears contextualized in Latin America. The purpose of this work is to argue the significance and place of the teacher's performance as a factor directly associated with educational quality. Some basic ideas are supported: namely, Latin America has not met basic goals in terms of equity and justice in access to education, which represents a burden on the work for the quality of this service; Educational quality is associated with a set of factors including economic, political, cultural, scientific and technological factors, as well as an important human factor: the teacher's performance, which is vital according to the position held. In that order, the limitations that are presented today in the initial and continuing teacher training process are pointed out, as well as the challenges that must be faced as part of their performance to provide a coherent response that implies a quality education in the present century and the social, cultural and technological changes that are experienced daily. This essay is the expression of a theoretical systematization, based on inquiries from various sources on the subject, in which reports from international organizations stand out for their value.